Syndemic, mental health and living with dependent persons in Latin America and Spain: a study with a gender perspective - Natalia López-Contreras; Tomás López-Jiménez; Laura Medina-Perucha; Brenda Biaani León-Gómez; Alessandra Queiroga Gonçalves; Olivia Janett Horna-Campos; Maria Sol Anigstein; Jakeline Ribeiro Barbosa; Mariana Pastorello Verotti; Olga Bardales-Mendoza; Karen M. Arteaga-Contreras; Anna Berenguera; et al. (Archives of Public Health)
Abstract Objective To analyze the sociostructural determinants associated with mental health problems during the lockdown period among populations residing in Brazil, Chile, Ecuador, Mexico, Peru, and Spain who lived with minors or dependents, approached from a gender perspective. Methods A cross-sectional study was conducted in six participating countries via an adapted, self-managed online survey. People living with minors and/or dependents were selected. Multivariate logistic regression models were estimated to assess the associations between sociostructural variables and mental health problems (anxiety (GAD-7) and/or depression (PHQ-9)). The analyses were stratified by sex and country. Results Out of a total of 39,006 people, 18,040 reported living with minors and/or dependents (73% women). In all countries, women reported worse mental health, with Spain having a lower prevalence. The risks of mental health problems in women in most countries are associated with poor housing conditions and performing care work. University education was associated with a protective factor. For men, risks were related to being younger, worsening working conditions and concerns about living together at home. Conclusions Women in Latin America who lived with dependents had worse outcomes than those in Spain did. It is necessary to develop intersectoral and social determinants strategies to prevent, protect and support the mental health of those who live with dependents and minors.